Is Motor Simulation Involved During Foreign Language Learning? A Virtual Reality Experiment. (8th October 2015) - Repetto, Claudia; Colombo, Barbara; Riva, Giuseppe
This article presents a study performed to investigate the role of simulation in second language learning while using a virtual environment. Participants were asked to explore a virtual park while learning 15 new Czech verbs (action verbs that describe movements performed with either the hand or the foot, and abstract verbs). This learning condition was compared with a baseline condition, where movements (either virtual or real) were not allowed. The goal was to investigate whether the virtual action (performed with the feet) would promote or interfere with the learning of verbs describing actions that were performed with the same or a different effector. The number of verbs correctly remembered in a free recall task was computed, along with reaction times and number of errors during a recognition task. Results show that the simulation per se has no effect in verbal learning, but the features of the virtual experience mediate it.